Determination of Saturated and Unsaturated Fatty Acids by Gas Chromatography in Linseed (Linum usitatissimum L.) Genotypes - Endes, Zuleyha; Akinerdem, Fikret; Musa Ozcan, Mehmet (Asian Journal of Chemistry, 2012)
The aim of this study is to determine the saturated and unsaturated fatty acids in nine varieties of linseed oil genotypes (Atalanta, Raulinus, Maroc SM, Avangard, Antares, Sari-85, P-Kulu, P-Cihanbeyli and P-Halfeti) grown in different sowing times (April 6, April 16, April 26, May 6). The main fatty acid components of genotypes identified by gas chromatography were linolenic acid (51 %), linoleic acid (13 %), oleic acid (22 %), palmitic acid (6 %), stearic acid (7 %), palmitoleic acid (1 %) and myristic acid (0.041 %). The growth of linseed was highly affected by the sowing times. According to the results, oil rates of genotypes were in the range of 31-35 and 13 % of this ratio was saturated, 23 % was monounsaturated and 64 % polyunsaturated fatty acids. It was also found that delaying sowing times caused decrease in the amount of saturated and polyunsaturated fatty acids and increase in the amount of monounsaturated fatty acids.